The role of technology acceptance model on RHB mobile banking - Abdul Halim Shah, Ahmad Adzri; Mahomed, Anuar Shah Bali; Mohsin Ali, Rana; Raja Nerina (International Journal of Scientific and Technology Research, 2019)
Mobile banking developments and trends in recent years had great impacts on banking sector worldwide. Therefore, the disruptive innovative technology has accelerated changes in the way of banking business. The purpose of this paper is to explore the role of Technology Acceptance Model on RHB Mobile Banking. The sample used in this study includes 85 responses of RHB Mobile Banking users collected through structured questionnaire distributed via cyberspace. For statistical analysis, structural equation model (SEM) approach was used. The present study suggests that mobile banking use increases as long as customer perceives it as useful tool. Findings confirmed that perceived usefulness, perceived ease of use and perceived trust were the key constructs for promoting mobile banking usage in Malaysia. Furthermore, the importance performance matrix analysis trust has seen the most important factor. Thus, banks can focus on cultivation of positive trust beliefs about mobile banking among prospect customers.